Promoter Targeting shRNA Suppresses HIV-1 Infection In vivo Through Transcriptional Gene Silencing - Kazuo Suzuki; Shinichiro Hattori; Katherine Marks; Chantelle Ahlenstiel; Yosuke Maeda; Takaomi Ishida; Michelle Millington; Maureen Boyd; Geoff Symonds; David A Cooper; Seiji Okada; Anthony D Kelleher (Elsevier, 2013)
Despite prolonged and intensive application, combined antiretroviral therapy cannot eradicate human immunodeficiency virus (HIV)-1 because it is harbored as a latent infection, surviving for long periods of time. Alternative approaches are required to overcome the limitations of current therapy. We have been developing a short interfering RNA (siRNA) gene silencing approach. Certain siRNAs targeting promoter regions of genes induce transcriptional gene silencing. We previously reported substantial transcriptional gene silencing of HIV-1 replication by an siRNA targeting the HIV-1 promoter in vitro. In this study, we show that this siRNA, expressed as a short hairpin RNA (shRNA) (shPromA-JRFL) delivered by lentiviral transduction of human peripheral blood mononuclear cells (PBMCs), which are then used to reconstitute NOJ mice, is able to inhibit HIV-1 replication in vivo, whereas a three-base mismatched variant (shPromA-M2) does not. In shPromA-JRFL-treated mice, HIV-1 RNA in serum is significantly reduced, and the ratio of CD4+/CD8+ T cells is significantly elevated. Expression levels of the antisense RNA strand inversely correlates with HIV-1 RNA in serum. The silenced HIV-1 can be reactivated by T-cell activation in ex vivo cultures. HIV-1 suppression is not due to offtarget effects of shPromA-JRFL. These data provide "proof-of principle" that an shRNA targeting the HIV-1 promoter is able to suppress HIV-1 replication in vivo.